The Endurance of Shareholder Value Maximization as the Preferred Corporate Objective - Inkpen, Andrew C.; Sundaram, Anant K. (Journal of Management Studies, 2022)
Abstract Sundaram and Inkpen (2004a, 2004b) proposed shareholder value maximization (SVM) as the preferred corporate objective since it alone impels the firm to implement strategies that enhance outcomes for all stakeholders. Goranova and Ryan (2021) argue that three recent developments – common ownership, decoupling of owners from managers, and greater divergence in shareholder interests – call into question our SVM view. We dispute their arguments: (i) The developments they cite are overplayed in the literature, and may not matter much for SVM; (ii) To the extent they do matter, their concern is less about SVM’s relevance as corporate objective but more whether these developments bias decisions towards the short‐term. We do not disagree since, after all, Sundaram and Inkpen (2004a) is solely about SVM for the long‐term ; (iii) If anything, Goranova and Ryan’s (2021) proposed solution of ‘strategic corporate governance’ can be viewed as an endorsement of the relevance and enduring primacy of SVM for the long‐term.